ACCURACY OF COMPUTER-AIDED IMPLANT SURGERY - Cosmin Cretu; Doriana Agop-Forna; Dimitris Bardi; Ioana Cristea; Cristina Dascãlu; Siminiuc Petruţa; Norina Forna (Romanian Society of Oral Rehabilitation, 2023)
Aim of study. This study aimed to assess the linear and angular discrepancies between planned and surgically placed implants using a dental-support 3D printed surgical guide. Materials and methods: Twenty implants were inserted into posterior maxillary and mandibular areas of 13 edentulous patients. CBCT exam was performed with Galileos Comfort Plus (Dentsply Sirona) 3D imaging unit. Intraoral scans were performed with PrimeScan (Dentsply Sirona) Implants positioning virtual planning was performed with treatment planning software Galileos Implant (Dentsply Sirona). The design and set-up of the dental-support surgical guide was performed with Blue Sky (Blue Sky Bio). Post-implant therapy the 3D spatial coordinates (at shoulder and apex) as well as angle inclination displacements of real implants were compared to virtual plans. The analysis was performed in OnDemand software calculating linear deviations in horisontal plane (mesiodistal, buccolingual) and vertical plane (apicocoronal) at shoulder and apex. Angular deviation was also measured. Statistical analysis was performed using the SPSS version 29.0 software package (SPSS Inc., Chicago, IL, USA). Categorical variables were presented as frequencies and percentages, and continuous variables as mean, standard deviation, minimal and maximal values. Results: Implant evaluation showed in average the following linear deviations in horisontal plan: at shoulder level (0,623 mm mesiodistal, 0,663 mm buccolingual); at apex level (0,436 mm mesiodistal, 0,663 mm buccolingual). In vertical plan (apicocoronal) the mean deviations were 0,054 mm at shoulder level, and -0,029 mm at apex level. A mean 4,710 angular global deviation was recorded. Conclusions. Digitally-assisted surgery with dental-support surgical guides is a predictable procedure for flapless implant surgical stage. Mean clinically acceptable liniar and angular deviation values between virtual implants and inserted implants were recorded. The maximum values of angle deviations highlight the need for flap surgery in areas with severe alveolar bone resorptions to prevent the errors in implant positioning.